Comparative studies of essential oils composition and cytotoxic activity of Valeriana jatamansi Jones. Issue 6 (2nd November 2021) - Maurya, Antim K.; Sharma, Anamika; Kumar, Kushal; Chander, Ram; Kumar, Ashish; Kumar, Dharmesh; Padwad, Yogendra S.; Chand, Gopi; Agnihotri, Vijai K.
ABSTRACT: The aim of this study was to investigate comparative essential oils (EOs) composition and cytotoxic activity of Valeriana jatamansi Jones, from wild growing samples at higher altitude and cultivated sample at lower altitude. Hydrodistilled EOs from the rhizomes of this herb were analyzed using Gas Chromatography with Flame Ionization Detector (GC-FID), Gas Chromatography/Mass Spectrometry (GC/MS), and Nuclear Magnetic Resonance ( 13 C NMR). Thirty-six diverse metabolites were characterized in EOs samples accounting 68.5–88.2% of the total oils. The extracted EOs were found to be enriched in patchouli alcohol (7.6–70.5%), β -bisabolol (17.2–21.4%), maaliol (0.3–28.1%) and α- bulnesene (1.4–8.5%). The obtained EOs were further evaluated for cytotoxic activity against human lung carcinoma (A549) and human skin carcinoma (A431) cancer cells. Isolated component (patchouli alcohol) and extracted oils were represented good to moderate cytotoxic activity. These findings showed that EOs of these plants could be employed in the field of flavour, fragrance and pharmaceutical applications.